Age Attenuates Leucine Oxidation after Eccentric Exercise - Kullman, E. L.; Campbell, W. W.; Krishnan, R. K.; Yarasheski, K. E.; Evans, W. J.; Kirwan, J. P. (International Journal of Sports Medicine, 2013)
Aging may alter protein metabolism during periods of metabolic and physiologic challenge. The purpose of this study was to assess the effects of age on whole-body amino acid turnover in response to eccentric exercise and hyperglycemia-induced hyperinsulinemia. 16 healthy men were divided into young (N=8) and older (N=8) groups. Protein metabolism was assessed using a [1-13C]-leucine isotopic tracer approach. Measures were obtained under fasted basal conditions and during 3-h hyperglycemic clamps that were performed without (control) and 48 h after eccentric exercise. Exercise reduced leucine oxidation in the younger men (P<0.05), but not in older men. Insulin sensitivity was inversely correlated with leucine oxidation (P<0.05), and was lower in older men (P<0.05). Healthy aging is associated with an impaired capacity to adjust protein oxidation in response to eccentric exercise. The decreased efficiency of protein utilization in older men may contribute to impaired maintenance, growth, and repair of body tissues with advancing age.
Keywords: age; amino acid metabolism; insulin resistance; physical activity